2021
DOI: 10.1136/bmjopen-2020-044228
|View full text |Cite
|
Sign up to set email alerts
|

BASAN index (Body mass index, Age, Sex, Arterial hypertension and Neck circumference) predicts severe apnoea in adults living at high altitude

Abstract: ObjectivesObstructive sleep apnoea (OSA)/hypopnoea syndrome is associated with serious and major multiorgan morbidities, particularly in its most severe forms. However, no severe OSA screening instruments are available for high altitude residents that enable adequate identification and clinical prioritisation of such patients. We aimed at developing a severe OSA prediction tool based on the clinical characteristics and anthropometric measurements of a clinical referral cohort living at 2640 m.a.s.l.DesignCohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…These findings may explain by the correlation between neck circumference and the severity of OSA. A previous study demonstrated that neck circumference is a predictor of OSA severity: mild (37.1 cm), moderate (38.0 cm), and severe (39.8 cm) with a p value of 0.0001 (Oliveros et al, 2021 ). The previous study found that severe OSA was associated with a reduction of TFF3 levels (Siber‐Hoogeboom et al, 2017 ).…”
Section: Discussionmentioning
confidence: 96%
“…These findings may explain by the correlation between neck circumference and the severity of OSA. A previous study demonstrated that neck circumference is a predictor of OSA severity: mild (37.1 cm), moderate (38.0 cm), and severe (39.8 cm) with a p value of 0.0001 (Oliveros et al, 2021 ). The previous study found that severe OSA was associated with a reduction of TFF3 levels (Siber‐Hoogeboom et al, 2017 ).…”
Section: Discussionmentioning
confidence: 96%
“…Firstly, it is specifically designed to screen moderate/severe OSA in patients with ACS. Population heterogeneity is a very important consideration, and studies have shown that arterial hypertension and neck circumference are important variables in patients with severe OSA living at high altitudes [ 10 ]. Sole et al found that traditional OSA predictors (eg, gender, Epworth score) performed poorly in more advanced COPD patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%